2021
DOI: 10.3390/app11062487
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Power Management Integrated Circuits for Ultrasound-Based Energy Harvesting in Implantable Medical Devices

Abstract: This paper aims to review the recent architectures of power management units for ultrasound-based energy harvesting, while focusing on battery-less implantable medical devices. In such systems, energy sustainability is based on piezoelectric devices and a power management circuit, which represents a key building block since it maximizes the power extracted from the piezoelectric devices and delivers it to the other building blocks of the implanted device. Since the power budget is strongly constrained by the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 49 publications
(86 reference statements)
0
19
0
Order By: Relevance
“…Interestingly, the most significant performance improvement was obtained with the CDN topology. Indeed, it was reported that with planar technology, this topology shows good VCE at the price of a reduced PCE with a 50 kΩ-load [6]. In our previous work, we already observed that the scaling from 90 nm to 32 nm was not so advantageous since the obtained VCE remained close to the one from the conventional CCDD topology for a PCE in the range of only 25-35%.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Interestingly, the most significant performance improvement was obtained with the CDN topology. Indeed, it was reported that with planar technology, this topology shows good VCE at the price of a reduced PCE with a 50 kΩ-load [6]. In our previous work, we already observed that the scaling from 90 nm to 32 nm was not so advantageous since the obtained VCE remained close to the one from the conventional CCDD topology for a PCE in the range of only 25-35%.…”
Section: Resultsmentioning
confidence: 71%
“…Indeed, a 50 Ω-antenna harvests an RF signal and transmits it to a rectifier by means of a matching impedance network [3,4]. Then, the rectifier or RF-DC converter provides a micropower DC signal to a Power Management Unit (PMU) to supply the chip (Figure 1) [5,6]. The most challenging step remains the rectifying stage that must produce DC with a low power supply.…”
Section: Introductionmentioning
confidence: 99%
“…An in‐depth review of power management integrated circuits has been published here. [ 141 ] Briefly, to further enhance the power harvesting capabilities of UPIs, electrical impedance matching can be employed. Impedance matching at a resonant frequency can be accomplished using an LC or shunt inductor or capacitor.…”
Section: Piezoelectric Ultrasound‐powered Implantsmentioning
confidence: 99%
“…Bootstrapped switches are widely used in many mixed-signal circuits [10][11][12][13]. For example, they are used in sample and hold circuits to achieve rail-to-rail switching functions [10,11], used in charge pump circuits to improve energy harvesting by node precharging [12,13], and so on. There are also reports on improving the performance of bootstrap switches [14][15][16].…”
Section: Introductionmentioning
confidence: 99%